Poverty and Social Exclusion in India : Overview - Das, Maitreyi Bordia (World Bank, Washington, DC, 2017)
The report’s main objective is to track development outcomes for three select groups - scheduled tribes (STs), scheduled castes (SCs), and women - that have traditionally faced exclusion in India. It asks the question: how did these groups fare over a period of rapid growth in India, primarily in the nineties; and were they able to break through the historically grounded inequalities that have kept entire generations among them trapped or did traps trump opportunities? It focuses on exclusion along three spheres - services, markets, and voice and agency. Within these too, the attempt is to highlight a few select issues that offer new insights. The report draws both on national data (national sample surveys (NSS) and national family health surveys (NFHS)) as well as qualitative work for its evidence, relying more on the latter to probe heterogeneity within states and groups and incipient processes that result in exclusion.